The Senoi of Perak - Edo, Juli (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The Senoi is one of three major groups of Orang Asli in Peninsular Malaysia. Administratively the Senoi is divided into six sub-groups comprising the Semai, Temiar, Chewong, Jah Hut, Semoq Beri, and Mah Meri, and live in communities across Perak, Kelantan, Terengganu, Pahang, and Selangor. Of the six sub-groups, only the Semai and Temiar traditionally occupy settlement in Perak. However, as a whole, the Semai can be found across a much larger area, ranging from the central parts of Perak to the areas further south occupying areas along the boundary of Selangor. The Temiar settlement begins from central Park and stretches up to the northeastern part of the state. According to the 1991 Census, the total population of the Semai people in Perak numbered approximately 17, 973 but the Census for the Temiar people showed that they numbered approximately 10,010.